Characteristics and Phylogenetic Analysis of the Complete Chloroplast Genome of the Cultivar Cypresses Hesperocyparis macrocarpa (Cupressaceae) - Son Le; Cuong Minh Le; Minh Trong Quang (Biomedical and Biotechnology Research Journal, 2025)
Background: Hesperocyparis macrocarpa (Hartw.) Bartel 2009 is a versatile hardwood species that exhibits a morphological resemblance to Cupressus tonkinensis, a threatened and endemic species in Vietnam. Because of the near depletion of its gene pool, conservation and development programs for C. tonkinensis have been initiated. As part of these efforts, Cypress has been introduced and cultivated in Vietnam. In this study, the chloroplast (cp) genome of H. macrocarpa was assembled and characterized for the first time. Methods: The leaves of H. macrocarpa were collected from Thanh Hoa Province, Vietnam. Genomic deoxyribonucleic acid (DNA) was extracted using a commercial purification kit, and sequencing was performed using a BGISEQ-50 sequencer. The obtained reads were assembled de novo using NOVOPlasty, and gene annotation was conducted using MITOS2. Phylogenetic analysis was performed on the IQ-TREE webserver using the maximum likelihood method based on the protein-coding genes (PCGs). Results: The complete cp genome of H. macrocarpa was 126,916 base pair in length, consisting of 110 genes in total, including 83 PCGs, 33 transfer RNA genes, and 4 Ribosomal RNA genes. Inverted repeat regions were absent from the H. macrocarpa cp genome. The overall guanine–cytosine content was 34.7%. Phylogenetic analysis revealed that H. macrocarpa was the earliest divergent species in the Hesperocyparis genus. Conclusion: This study provided the first cp genome of H. macrocarpa and enriched the genetic resources of the Hesperocyparis genus. The plastome data provided valuable insights for genetic research across various fields, including evolutionary phylogenetics, taxonomy, conservation, and DNA barcoding for species identification.